2014
DOI: 10.1117/1.jmi.1.3.033504
|View full text |Cite
|
Sign up to set email alerts
|

Calibration-free coronary artery measurements for interventional device sizing using inverse geometry x-ray fluoroscopy:in vivovalidation

Abstract: Proper sizing of interventional devices to match coronary vessel dimensions improves procedural efficiency and therapeutic outcomes. We have developed a method that uses an inverse geometry x-ray fluoroscopy system [scanning beam digital x-ray (SBDX)] to automatically determine vessel dimensions from angiograms without the need for magnification calibration or optimal views. For each frame period (1/15th of a second), SBDX acquires a sequence of narrow beam projections and performs digital tomosynthesis at mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The method performs a local clustering of pixels using their color values and spatial locations. Figure 2 shows an X-ray frame segmented using the SLIC superpixel algorithm 1 . Superpixels have been used within graph-based methods such as normalized cut [13] and random walks [14], where they simplify the graph size and the retrieval of the optimal solution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The method performs a local clustering of pixels using their color values and spatial locations. Figure 2 shows an X-ray frame segmented using the SLIC superpixel algorithm 1 . Superpixels have been used within graph-based methods such as normalized cut [13] and random walks [14], where they simplify the graph size and the retrieval of the optimal solution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These measurements include computing the vessel segment length [1], detecting stenosis [2] and estimating the severity of a stenosis by measuring the vessel's diameter [3]. Segmenting and tracking the artery along the moving angiography sequence is a key step for measuring the artery and assessing its dynamics in the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time tomosynthesis offers novel capabilities that are unavailable with conventional fluoroscopy. For example, it has been shown that the depth resolution inherent to SBDX tomosynthesis can be exploited to perform real-time 3D catheter tracking, 7,8 3D vessel analysis, 9 stereoscopic fluoroscopy, 10 and lung tomosynthesis. 11 However, inverse geometry fluoroscopy also requires a different approach to forming a 2D display analogous to conventional fluoroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…1A). 1,2 The inverse geometry design provides SBDX with an inherent real-time tomosynthesis capability 2 that has been exploited for a number of applications including frame-by-frame 3D tracking of high-contrast objects such as cardiac catheters, 3 calibration-free vessel measurements for device sizing, 4 and stereoscopic fluoroscopy. 5 …”
Section: Introductionmentioning
confidence: 99%